GROWTH RESPONSE OF CELERY PLANTS (Apium graveolens L.) AGAINST THE COMBINED APPLICATION OF LIQUID ORGANIC FERTILIZERS AND COMPOST FERTILIZERS - Otovina Gebze; Jefri Sembiring; Diana S Susanti; joana mendes (Musamus Journal of Agrotechnology Research, 2022)
Abstract The purpose of this study was to analyze the growth of celery (Apium graveolens L.) in the application of a combination dose of liquid organic fertilizer and compost. This research was conducted at the Screen House Laboratory of Agrotechnology, Faculty of Agriculture, Musamus University, Merauke in June-September 2018. This study used a factorial randomized block design (RAKF). The first factor is compost and the second factor consists of liquid organic fertilizer. The two factors after being combined obtained 16 treatments which were repeated 3 times to obtain 48 treatment units. Based on the results of the study, it was concluded that the analysis of the growth variance of celery on the application of a combination dose of liquid organic fertilizer and compost showed no significant effect. On the variable plant height, the combination treatment of A3N3 (compost 60 g/plant and POC 4 ml/liter) gave the highest plant height of 26.00 cm, and the variable number of leafstalks in the A3N0 treatment (compost 60 g/plant and POC 0 ml/liter) gave The result of the number of petioles was 14.33 strands, and the variable number of tillers of A3N0 treatment plants (60 g compost/plant and 4 ml POC/liter) gave 2.67 tillers. Keywords: Apium graveolens L, POC, Compost